Early detection of HCC in patients with cirrhosis using AI; a Systematic Review - Asfia Arham Khursheed; Muhammad Rizwan Khan (Journal of the Pakistan Medical Association, 2024)
Introduction: Hepatocellular carcinoma constitutes for approximately 75% of primary cancers of liver. Around 80- 90% of patients with HCC have cirrhosis at the time of diagnosis. Use of AI has recently gained significance in the field of hepatology, especially for the detection of HCC, owing to its increasing incidence and specific radiological features which have been established for its diagnostic criteria. Objective: A systematic review was performed to evaluate the current literature for early diagnosis of hepatocellular carcinoma in cirrhotic patients. Methods: Systematic review was conducted using PRISMA guidelines and the relevant studies were narrated in detail with assessment of quality for each paper. Results: This systematic review displays the significance of AI in early detection and prognosis of HCC with the pressing need for further exploration in this field. Conclusion: AI can have a significant role in early diagnosis of HCC in cirrhotic patients Keywords: Carcinoma, Hepatocellular, Liver Neoplasms, Gastroenterology, Liver Cirrhosis, Prognosis, cirrhosis, radiological features.